Evaluating the effectiveness of the open-access ChemWiki resource as a replacement for traditional general chemistry textbooks. Issue 4 (25th September 2015) - Allen, Gregory; Guzman-Alvarez, Alberto; Smith, Amy; Gamage, Alan; Molinaro, Marco; Larsen, Delmar S.
Abstract : Open educational resources (OERs) provide a potential alternative to costly textbooks and can allow content to be edited and adapted to a variety of classroom environments. At the University of California, Davis, the OER "ChemWiki" project, as part of the greater STEMWiki Hyperlibrary, was developed to supplant traditional post-secondary chemistry textbooks. The effectiveness of using this OER was assessed by comparing two general chemistry classes, one using ChemWiki and one using a traditional textbook, during the spring quarter of 2014. Student performance was measured using common midterms, final, and a pre/post content exam. We also employed surveys, the Colorado Learning Attitudes about Science Survey (CLASS) for Chemistry, and a weekly time-on-task survey to quantify students' attitudes and study habits. The effectiveness of the ChemWiki compared to a traditional textbook was examined using multiple linear regression analysis with a standard non-inferiority testing framework. Results show that the performance of students who were assigned readings from the ChemWiki section was non-inferior to the performance of students in the section who were assigned readings from the traditional textbook, indicating that the ChemWiki does not substantially differ from the standard textbook in terms of student learning outcomes. The results from the surveys also suggest that the two classes were similar in their beliefs about chemistry and minimal overall study time. These results indicate that the ChemWiki is a viable cost-saving alternative to traditional textbooks.